Can gender differences in distributional preferences explain gender gaps in competition? - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We design an experiment to examine whether egalitarian preferences, and in particular, behindness aversion as well as preference for favourable inequality affect competitive choices differently among males and females. We find that selection into competitive environments is: (a) negatively related to egalitarian preferences, with smaller negative impacts of being egalitarian on females' choice of the tournament wage scheme, and (b) negatively associated with behindness aversion and positively related to preference for favourable inequality, with significant gender differences in the impact of these distributional preferences. Once we allow for the impact of distributional preferences, behavioural, personality, and socioeconomic characteristics to vary by gender, the pure gender effect is explained away. We find that gender gaps in distributional preferences along with selected personality traits are the most relevant explanations for gender differences in willingness to compete. This is an important result as these characteristics are per se malleable and amenable to policy interventions.
Keywords: C91; D03; D63; J16; 330; competitiveness; distributional preferences; gender differences